A comparative analysis of a brand's promise compared to the actual service experience, has on Brand Equity, using Keller's Brand Equity model: Telkom - Davin, Edin (The IIE, 2017)
This study will conduct a comparative thematic analysis amongst Telkom customer service hubs in Johannesburg and the brand promise made on the official Telkom website to determine if customer service experiences impact Telkom’s brand equity through the use of Keller’s Brand Equity Model. Work has been done on the importance of customer service to a brand, such as assumptions that there is a direct link between brand satisfaction and customer loyalty (Martisiute, Vilutyte & Grundey, 2010). Theorists including Torres Moraga et al (2008) agree with the belief that the brand will impact customer satisfaction. Martisiute et al (2010) state that customer satisfaction leads to loyal customers. The study follows an interpretivist paradigm within a qualitative approach. Two data collection methods are used field research using in-depth interviews and unobtrusive research using Qualitative content analysis. The methods used to analyse the data are thematic content analysis and qualitative content analysis. Findings indicate that Telkom’s brand promise according to their website is “to connect people to a better life”. Most consumers interviewed did not understand what a brand promise was and had not found out for themselves about Telkom’s brand promise. There is a discrepancy between the brand promise and the service offered by Telkom. Maltitz (2016) states that South African consumers are hooked onto particular brands for no good reason even when there are better products, which will not even be considered. The consequence of these consumers is that they ignore the failures of the brand, giving the brand power and unconditional consumers even when they cannot or do not deliver on their promise (Glance, 2014).
Keywords: Customer Service; Brands; Brand Equity; Brand Promise; Consumer Behaviour; Telecommunications; Digital Communication